The Body as Touch: Speaking Death and Dying in Queer Theory and Religion - Coble, Richard (Pastoral psychology, 2015)
This article examines the possibility of feeling the body's deadly touch via speech. Beginning with my own experiences as a hospital chaplain, the article explores psychological and political theories of the separation between the ego and the body and the collapse between the two in death. The final two sections examine contrasting theories that seek to bring bodily dissolution to speech. I contrast theorists Lee Edelman and Leo Bersani with the formulations of religious language by Julia Kristeva and Jean-Luc Nancy to examine faith's ambiguous potential to bring death to speech amidst the realities of dying bodies.